REPRESENTATIVITY OF SELECTION OF THE DETRITAL ACCESSORY MINERALS WITH SINGLE-GRAIN GEOCHEMICAL IN-DEPTH STUDY THEIR POPULATIONS - BUNKEVYCH, O.; SHNIUKOV, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Single-grain geochemical study of accessory minerals detrital populations is a powerful tool for sedimentary provenance including source rocks determination and their age dating. Estimation of representative amount of analysed grains sampling is one of the problems of this method. Technique for this problem solving under various realistic conditions was suggested.